2015
DOI: 10.1021/acs.nanolett.5b03277
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Observation of Reconstruction Dynamics on TiO2(001) Surface under Oxygen via an Environmental Transmission Electron Microscope

Abstract: The surface atomic structure has a remarkable impact on the physical and chemical properties of metal oxides and has been studied extensively by scanning tunneling microscopy. However, acquiring real-time information on the formation and evolution of the surface structure remains a great challenge. Here we use environmental transmission electron microscopy to directly observe the stress-induced reconstruction dynamics on the (001) surface of anatase TiO2. Our in situ results unravel for the first time how the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
132
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(139 citation statements)
references
References 38 publications
7
132
0
Order By: Relevance
“…However, a deep understanding of the mechanism of the electrocatalytic process is still lacking, and the real active sites are poorly recognized. More recently, several high‐end instruments, such as in situ and micro‐testing‐technologies have been designed, which can provide more in‐depth information about nanomaterials even at the atomic scale/microscale . These advanced instruments can help us to study the growth process of electrocatalysts, observe the electrochemical reaction process directly, and analyze the reaction mechanisms accurately .…”
Section: Introductionmentioning
confidence: 99%
“…However, a deep understanding of the mechanism of the electrocatalytic process is still lacking, and the real active sites are poorly recognized. More recently, several high‐end instruments, such as in situ and micro‐testing‐technologies have been designed, which can provide more in‐depth information about nanomaterials even at the atomic scale/microscale . These advanced instruments can help us to study the growth process of electrocatalysts, observe the electrochemical reaction process directly, and analyze the reaction mechanisms accurately .…”
Section: Introductionmentioning
confidence: 99%
“…Environmental TEM (ETEM) is useful for investigating dynamic behavior during the nanoscale structural and chemical evolution of materials under reactor conditions. It can reveal the reaction pathways of metal NPs via direct observations of intermediate phases and/or structures [18][19][20][21][22][23]. Uchiyama et al [18] reported that the change in morphology correlated well with the catalytic activity of supported Au NPs on CeO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Uchiyama et al [18] reported that the change in morphology correlated well with the catalytic activity of supported Au NPs on CeO 2 . Yuan et al [19] studied the stressinduced surface reconstruction of anatase TiO 2 in the presence of oxygen via ETEM. However, the kinetics of the oxidation of Co NPs have been less studied, particularly at the atomic scale.…”
Section: Introductionmentioning
confidence: 99%
“…Through in situ TEM study, the growth processes of NWs with metal catalysis1011 and two-dimensional MoS 2 flakes12 have been carefully demonstrated, and the complicated physicochemical processes related to the nanomaterial growth have also been well in situ monitored and explained at atomic level, such as the coalescence of nanocrystals1314, lateral atoms displacements and rotations151617, and surface reconstructions18, etc . Recently, with in situ environmental TEM, the noncatalytic metal oxide NW growth through thermal oxidation has been observed with lattice resolution, and the NWs have been suggested to grow through the oscillatory mass transport process19 or layer-by-layer growth induced by surface nucleation at the edge of twin boundary ridges20.…”
mentioning
confidence: 99%